Profil asam lemak abon ikan dengan penambahan buah nangka selama penyimpanan: Fatty acid profile of fish floss with the addition of jackfruits during storage - Sukmiwati, Mery; Diharmi, Andarini; Sari, Noor Ira (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Fish floss is a product made from seasoned fish meat to add flavor. The addition of jackfruit to fish floss is expected to add flavor and aroma, increase the nutritional value, and increase the variety of fish floss products. This study aimed to determine the quality characteristics of shredded catfish and jackfruit during storage. The catfish to jackfruit ratio was 2:1 (w/w). The test parameters included the fat content, free fatty acids, peroxide value, and total fatty acid content. The study used a completely randomized design (CRD) with different storage length treatments, namely 15, 30, and 45 days, with three replications. Different storage times showed that the fat content is 23.39–23.45%, the free fatty acids are 0.34–0.38%, and the peroxide value in jackfruit shredded fish increased after 45 days of storage, with a value of 5.74–8.26 meq/kg. The total fatty acid content in jackfruit shreds during storage increased by approximately 80.58–88.48%. The highest fatty acid content was oleic acid (33.36–36.57%), while the lowest was pentadecanoic acid (0.03–0.04%) and arachidonic acid (0.03–0.04%).